From economic to legal competition : new perspectives on law and institutions in Europe - Marciano, Alain; Josselin, Jean-Michel . European Association of Law and Economics (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2003)
The idea of legal competition as a decentralized market process of law provision has earned an indisputable legitimacy among economists. This book presents a debate concerning the merits of and conditions for a competitive provision of law, with a special focus on institutions in Europe.
Includes bibliographical references and index.
oif 03/03/15
Loan
Keywords: Legislation -- Economic aspects Competition Legislation -- Economic aspects -- European Union countries. Law firms -- Europe